Characterization of mutation spectrum and identification of novel mutations in ATP7B gene from a cohort of Wilson disease patients: Functional and therapeutic implications. Issue 12 (16th September 2018) - Kumari, Niti; Kumar, Aman; Thapa, Babu Ram; Modi, Manish; Pal, Arnab; Prasad, Rajendra
Abstract: Wilson disease (WD), a copper metabolism disorder, occurs due to the presence of mutations in the gene encoding ATP7B, a protein that primarily facilitates hepatic copper excretion. A better understanding of spectrum and functional significance of ATP7B variants is critical to formulating targeted and personalized therapies. Henceforth, we screened and sequenced 21 exons of ATP7B gene from 50 WD patients and 60 healthy subjects. We identified 28 variants comprising, seven novels in 20% alleles, while eight variations affecting 23% alleles were first time reported in Indian cohort. The c.813C>A, p.(Cys271*) (10%) was the most frequent mutation. Bioinformatics analysis revealed five of seven novel variants viz. c.1600C>A, p.(Pro534Thr); c.1616C>A, p.(Pro539His); c.1924G>T, p.(Asp642Tyr); c.2168G>C, p.(Arg723Thr); c.2174G>C, p.(Arg725Thr) resulted in protein misfolding. Sequence conservation analysis of ATP7B regions containing novel variants documented an evolutionarily conserved nature. Functional analysis of these novel variants in five different cell lines lacking inherent ATP7B expression demonstrated sensitivity to CuCl2 ‐treatment, experiencing augmented cellular copper retention and decreased copper excretion as well as ceruloplasmin secretion to that of wildtype‐ ATP7B expressing cells. Interestingly, pharmacological chaperone 4‐phenylbutyrate, a clinically approved compound, partially restored protein function of ATP7B mutants. These findings might enable novel treatment strategies in WD by clinically enhancing the protein expression of mutant ATP7B with residual copper export activity. Abstract : Wilson disease exhibits clinical heterogeneity due to presence of various mutations in the ATP7B gene, leading to copper‐toxicity, rendering the available treatment procedure less effective and requires specific therapeutic alternatives. We report 21 mutations, of which, eight were never reported earlier in Indian population and seven are novel variants. Five novel variants resulted in functional decline of ATP7B due to protein misfolding. However, treatment with 4‐phenylbytyrate successfully restored partial ATP7B functions, thereby providing a therapeutic option for future consideration.